Penerapan Pendekatan Pembelajaran Matematika Realistik (PMR) Dalam Menyelesaikan Permasalahan Kontekstual Materi Bilangan Bulat Kelas VII SMP - Hasna Nisa; Silviana Tri Cahyani; Moch. Rhizky Iznaeny Novan (JUMAT: Jurnal Matematika, 2025)
This study aims to describe the process of solving contextual problems of integers in class VII junior high school through the application of Realistic Mathematics Education (PMR) approach. The research method used was descriptive qualitative. This research instrument used LKPD. The results showed that grade VI students can solve contextual problems seen from the horizontal mathematization process and vertical mathematization. Based on the results of the study, Grade VI students at one of the elementary schools in Kediri City have been able to solve contextual problems on whole number material with the PMR approach.